BRIDGING EDUCATIONAL GAPS: EDUCATION ACCESS POLICY FOR ALL CHILDREN - Henny; Noneng Nurhayani; Marwah (Adisam Publisher, 2024)
Education gaps are a crucial problem that impedes sustainable human resource development. The research aims to identify effective policies that can bridge educational gaps and ensure inclusive access to education for all children. The research method in this research is literature, by exploring various sources of journals and other documents. The results show that; first, there is a significant relationship between the level of investment in education and the quality of access to education; second, policies that prioritize inclusive education and learning diversity can accelerate the reduction of educational gaps; and third, the integration of technology into education has been found to be an important factor in improving the reach and affordability of education. In addition, collaboration among stakeholders including governments, business communities, non-profit organizations, and civil society groups, is needed to implement and support effective educational programmes. Finally, regular monitoring and evaluation of existing policies is key to ensuring sustained adjustment and improvement to educational practices. The findings underline the importance of a holistic and contextualized approach in an effort to reduce educational gaps.